2018
DOI: 10.1128/jcm.00067-18
|View full text |Cite
|
Sign up to set email alerts
|

BmGPAC, an Antigen Capture Assay for Detection of Active Babesia microti Infection

Abstract: Human babesiosis is an emerging zoonotic infectious disease caused by intraerythrocytic protozoan parasites of the genus Most cases of human babesiosis are caused by and often manifest in individuals over the age of 50 years or in patients with a compromised immune system. Patients who develop symptomatic infections usually experience months of asymptomatic infection after the acute infection has resolved. About one-fifth of-infected adults never develop symptoms. These asymptomatically infected individuals so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…The immunodominant BmGPI12 of B. microti is encoded by a member of the bmn multigene family and is one of the most highly expressed genes of the parasite during its development within red blood cells (Lodes et al, 2000; Cornillot et al, 2012, 2016; Silva et al, 2016). Consistent with the secretion of BmGPI12 from the parasite into the red blood cytoplasm and subsequently into the host (Luo et al, 2011, 2012; Cornillot et al, 2016; Thekkiniath et al, 2018), immunoblot analyses using anti-BmGPI12 antibodies on blood collected from mice and fractionated to collect plasma (S), erythrocyte cytoplasm (H), and membrane (P) fractions showed the presence of BmGPI12 in all three fractions from animals infected with B. microti strains (LabS1 or PRA99) (Fig 1A), but not from uninfected animals (Fig 1A). As a control, immunoblot analyses conducted using a monoclonal antibody against the mouse erythrocyte membrane protein, TER-119 (glycophorin A–associated protein [Ly-76]), identified this protein in the membrane (P) fractions of both uninfected and B. microti –infected erythrocytes (Kina et al, 2000), but not in the plasma or erythrocyte cytoplasm fractions (Fig 1A).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The immunodominant BmGPI12 of B. microti is encoded by a member of the bmn multigene family and is one of the most highly expressed genes of the parasite during its development within red blood cells (Lodes et al, 2000; Cornillot et al, 2012, 2016; Silva et al, 2016). Consistent with the secretion of BmGPI12 from the parasite into the red blood cytoplasm and subsequently into the host (Luo et al, 2011, 2012; Cornillot et al, 2016; Thekkiniath et al, 2018), immunoblot analyses using anti-BmGPI12 antibodies on blood collected from mice and fractionated to collect plasma (S), erythrocyte cytoplasm (H), and membrane (P) fractions showed the presence of BmGPI12 in all three fractions from animals infected with B. microti strains (LabS1 or PRA99) (Fig 1A), but not from uninfected animals (Fig 1A). As a control, immunoblot analyses conducted using a monoclonal antibody against the mouse erythrocyte membrane protein, TER-119 (glycophorin A–associated protein [Ly-76]), identified this protein in the membrane (P) fractions of both uninfected and B. microti –infected erythrocytes (Kina et al, 2000), but not in the plasma or erythrocyte cytoplasm fractions (Fig 1A).…”
Section: Resultssupporting
confidence: 56%
“…Proteomic, immunoproteomic, and genomic efforts used to search for major antigens of the parasite, which could be used as vaccines or diagnostic biomarkers, identified several antigens of B. microti that trigger a strong host immune response in mice and humans (Molestina et al, 2002; Cornillot et al, 2016; Silva et al, 2016; Elton et al, 2018). Among these, BmGPI12 (BmSA1) has been shown to trigger the strongest IgM and IgG responses and has been successfully used as a diagnostic marker of active B. microti infection (Thekkiniath et al, 2018). Although BmGPI12 and several other B. microti antigens carry an N-terminal signal peptide, sequence analysis showed that they lack canonical PEXEL ( Plasmodium export element) or PEXEL-like motifs found in secreted proteins of other apicomplexan parasites such as P. falciparum and Babesia bovis (Boddey et al, 2016; Gallego-Lopez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Both LC-MS/MS and secretion assays showed the presence of BmSA1 in the in vitro supernatant, indicating that BmSA1 exists in B. microti in two forms. This characteristic was consistent with that of most merozoite surface coat proteins in apicomplexan parasites (Man et al, 2017;Thekkiniath et al, 2018). One of the two existing forms is focused on the GPI-attachment site, where the proprotein cleavage occurs and which localizes a few amino acids before the C-terminal hydrophobic domain.…”
Section: Discussionsupporting
confidence: 80%
“…Babesia microti surface antigen 1 (BmSA1)has been reported as a diagnostic marker with high reactivity (Cornillot et al, 2016), and the ELISA detection method has also been established (Luo et al, 2011;Thekkiniath et al, 2018). However, there is no relevant report on its function or its specific role in parasite invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Publication of the full B. microti genome in 2012 has enabled identification of higher copy number detection targets, allowing the routine detection of less than 10 B. microti parasites per ml of blood [18,20]. Additional technological advances such as sample concentration, high copy detection targets such as BMN multigene family members, and bead-based target capture may further enhance the sensitivity of NAT assays [21,22]. Detection of Babesia antigen(s) offers additional markers of active infection.…”
Section: Babesia Microti Detection Toolsmentioning
confidence: 99%